1998
DOI: 10.1094/mpmi.1998.11.3.228
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Expression of Septoria lycopersici Tomatinase in Cladosporium fulvum: Effects on Compatible and Incompatible Interactions with Tomato Seedlings

Abstract: The anti-fungal, steroidal, glycoalkaloid saponin, alpha-tomatine, is present in uninfected tomato plants in substantial concentrations, and may contribute to the protection of tomato plants against attack by phytopathogenic fungi. In general, successful fungal pathogens of tomato are more resistant to alpha-tomatine in vitro than fungi that do not infect this plant. For a number of tomato pathogens, this resistance has been associated with the ability to detoxify alpha-tomatine through the action of enzymes k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…Wild Solanum species may have several steroid glycoalkaloids, including α-solanine and α-chaconine, which have been previously related to resistance to a range of pests and pathogens (Zhuchenko et al, 1975;Flanders et al, 1992;Melton et al, 1998;Ronning et al, 2000). Steroid glycoalkaloids have been shown to be toxic to nematodes (Zhuchenko et al, 1975;Allen & Feldmesser, 1970) and, speculatively, the presence of such glycoalkaloids in higher concentrations may result in the roots being inherently unattractive.…”
Section: Discussionmentioning
confidence: 99%
“…Wild Solanum species may have several steroid glycoalkaloids, including α-solanine and α-chaconine, which have been previously related to resistance to a range of pests and pathogens (Zhuchenko et al, 1975;Flanders et al, 1992;Melton et al, 1998;Ronning et al, 2000). Steroid glycoalkaloids have been shown to be toxic to nematodes (Zhuchenko et al, 1975;Allen & Feldmesser, 1970) and, speculatively, the presence of such glycoalkaloids in higher concentrations may result in the roots being inherently unattractive.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Cladosporium fulvum sensitive to ␣-tomatine can successfully induce disease in tomato. However, the transformants of C. fulvum expressing a heterologous expression of cDNA encoding tomatinase from Septoria lycopersici showed increase in sporulation in susceptible tomato lines and the symptoms caused were more severe in resistant lines compared to wild-type (Melton et al 1998).…”
Section: Enzymes Produced By Fungal Pathogensmentioning
confidence: 98%
“…The experiment was perperformed to detect α-tomatine in laboratory. The trial was conducted with a modified method of Melton et al (1998) and designed in Completely Randomized Design (CRD) with six treatments and three replications. Twenty-day-old seedlings var.…”
Section: Microbial Elicitors Inducing Plant Immunitymentioning
confidence: 99%
“…High quantity of -tomatine was detected from fresh green fruits as 0.9-55 mg/100 g plant fresh weight. Moreover, Melton et al (1998) reported that tomato seedlings var. Moneymaker Cf4 and Cf5at 11 day-old were inoculated with conidial suspension of Cladosporium fulvum at concentration as 5 × 10 5 conidia/ml.…”
Section: Introductionmentioning
confidence: 99%